The Relationship Between Organizational Culture and Knowledge Management in Educational-Therapeutic Hospitals (Case study Hamadan Educational-Therapeutic Hospitals in 2017) - Akbar Bahmani; Amin Biglarkhani; Gholam Hossein Fallahinia; Fatemeh Shirani (Hamadan University of Medical Sciences, 2018)
Introduction: Knowledge management in health care system can reduce medical errors, increase the quality of care, organizational learning and promote cooperation, innovation and cause cost reduction. The success of successful organizations lies in the organizational culture and employees' beliefs. The aim of this research was to investigate the relationship between organizational culture and knowledge management in Hamadan educational-therapeutic hospitals. Methods: The present study was a correlational study-related survey which was carried out in a cross-sectional way on 300 nurses in Hamadan's educational-therapeutic hospitals in 2017. Robbins organizational culture questionnaires and Nanoka Knowledge Management have been used to collect information. Data were analyzed using SPSS24 and descriptive (mean, deviation and variance) and analytical (Pearson correlation coefficient) methods were used. Results: In this study, the organizational culture of nurses (with a score of 2.5) and knowledge management (with score of 3.16) were in appropriate conditions. There was a positive and significant relationship between organizational culture and knowledge management (r = 0.639, P=0.001). All components of organizational culture with knowledge management have a positive and significant correlation. Conclusion: According to the results of the study, if organizational culture and its components are improved, the progress and improvement of knowledge management will increase the quality of health care services. It is suggested that in the process of establishing knowledge management in medical centers, attention should be paid to the structural and cultural dimensions of the organization, in particular the development of individual creativity and leadership style, coherence and integrity.